Mielensä muuttamisesta - Vainio, Olli-Pekka (Annales Academiae Scientiarum Fennicae, 2023)
It is a fact that we change our minds many times during our lives. However, changing our minds can potentially call our cognitive processes into question. How do we know if the change is for the better? In the worst case, our fickleness calls into question our own ability to evaluate the foundations of our worldviews. However, it is not justified to claim that worldviews have no truth value. Although comparing worldviews is difficult, it is still natural to assume that there can be a meaningful public debate about their foundations. However, this requires a public and open communal process that broadly manifests intellectual virtues and tolerance as it is common for humans to disagree about many things, which may even appear obvious to some.